New Imperialism or New Capitalism? - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2004)
Over the past century, the institution of 'capital' and the process of its 'accumulation' have been fundamentally transformed. By contrast, the theories that explain this institution and process have remained largely unchanged. The purpose of this mimeograph is to address this mismatch. Using a broad brush, we outline a new, power theory of capital and accumulation. We use this theory to assess the changing meaning of the corporation and the capitalist state, the new ways in which capital gets accumulated and the specific historical trajectory of twentieth-century capitalism up to the present.
Keywords: 330; arms; accumulation; capital flow; capitalism; conflict; corporation; crisis; distribution; elite; energy; finance; globalization; growth; imperialism; GPE; liberalism; Marxism; Middle East; military; national interest; neoclassical economics; neoliberalis